Research of Applying EHL Stress to Gear Strength Design - Xia Boqian; Liu Yanlong; Liu Haoming (Jixie chuandong)
A research of applying EHL stress to gear contact strength design. The design formulas of gear contact strength are given based on the EHL stress fitting formulas. The influence of various influencing factors such as load,speed,and lubricating oil viscosity on design result is investigated,and the design results respectively based on EHL stress and Hertz stress are compared. The results indicate that like Hertz stress,EHL stress can be also taken as the design basis for contact strength design,and the design result based on EHL center stress fitting formula is very close to that based on Hertz stress formula,but in case of high speed,because EHL spike stress is much bigger than EHL center stress,the EHL spike stress should be considered as the design consideration of gear contact strength.